2020
DOI: 10.1007/s00227-020-03738-2
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface phytoplankton community response to nutrient and light changes

Abstract: The sea surface microlayer (SML) is the boundary layer between the ocean and the atmosphere and plays a unique role in marine biogeochemistry. Phytoplankton communities in this uppermost surface layer are exposed to extreme ultraviolet (UV) radiation and potentially high nutrient supplies. In order to understand the response of SML communities to such contrasting conditions, we conducted experiments at three different sites, the North Sea (open ocean) and two sites, outer and middle fjord, in the Sognefjord, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…In our study, the PPEUK biomass dominance by the Picocryptophytes during the MON could be explained by their ability to sustain adverse and light-limited environments as they possess physiological adaptations such as the green lightharvesting phycobiliproteins and photoacclimation [50], as corroborated by the negative and positive correlation with the SD depth and the total chl-a, respectively. A higher biomass yield and a lower growth rate under the low light condition for phytoplankton have been shown with N and P additions [51]. In our study, the positive correlation of its abundance with NH during the PrM could suggest its capability to utilize all kinds of inorganic nutrients.…”
Section: Picoeukaryotic Abundance and Biomass: A Global Comparisonsupporting
confidence: 60%
“…In our study, the PPEUK biomass dominance by the Picocryptophytes during the MON could be explained by their ability to sustain adverse and light-limited environments as they possess physiological adaptations such as the green lightharvesting phycobiliproteins and photoacclimation [50], as corroborated by the negative and positive correlation with the SD depth and the total chl-a, respectively. A higher biomass yield and a lower growth rate under the low light condition for phytoplankton have been shown with N and P additions [51]. In our study, the positive correlation of its abundance with NH during the PrM could suggest its capability to utilize all kinds of inorganic nutrients.…”
Section: Picoeukaryotic Abundance and Biomass: A Global Comparisonsupporting
confidence: 60%
“…Besides, earlier studies [ 93 , 94 ] have described that the SML is dominated by diatom, cryptophytes, and dinoflagellates species. Indeed, various species of dinoflagellates and diatom are reported to express eCA [ 18 , 76 , 95 ].…”
Section: Enrichment Of Eca In the Sea Surface Microlayermentioning
confidence: 99%
“…Because of the unique location of the SML between the ocean and atmosphere, the communities in this layer are likely to be the first to be exposed to climate-related changes. For instance, previous studies have shown that light limitation affects growth rates and biomass in SML communities [ 95 ], and high nutrient loads changed the density and composition of SML communities [ 113 ]. Incomplete understanding of the C i acquisition strategy in the SML community’s response to future climate change leads to difficultly in predicting the global chemical enhancement of CO 2 and biogeochemical cycling by eCA.…”
Section: Enrichment Of Eca In the Sea Surface Microlayermentioning
confidence: 99%
“…Yet, for Norwegian coastal waters, peak spring phytoplankton bloom has been delayed by 22 days over the past century, which was attributed to coastal darkening (Opdal et al, 2019;Opdal et al, 2023). Mustaffa et al (2020) studied the relationship between light intensity and phytoplankton growth rates in the Sognefjord at the Norwegian west coast, impacted by freshwater inputs from several rivers. They found that increased light intensity led to higher phytoplankton growth rates in the central and outer fjord, but with no effect on phytoplankton in the open ocean, where the impact of terrestrial DOM is marginal.…”
Section: Introductionmentioning
confidence: 99%